Impact of structural eurocodes on steel and composite structures - Jin, Y. F. (2014)
The introduction of Structural Eurocodes to replace the existing British Standard design codes will benefit the construction industry in the long run. However, in the short term, to help our engineers migrate over to the new Eurocodes, it is useful to conduct a comparative study on both Eurocodes and British Standards to identify some of the key changes and impact on the performance of the steel and composite structures. In this connection, this paper investigates five key design aspects comprising material properties, flexural buckling resistance of compression members with Grade S460 steel, shear buckling resistance of plated structures, web bearing and buckling resistance of the plated structures under transverse force and lateral-torsional buckling of composite beam. It is found that the flexural buckling resistance, web bearing and buckling resistance and lateral-torsional buckling resistance determined from Eurocodes 3 and 4 are much larger than those from BS5950. However, for shear buckling resistance of plated structures, Eurocode 3 produced a lower value compared to BS5950, and for shear resistance of headed stud, Eurocode 4 produced a lower value compared to BS5950-3.1.